Ectoparasites in Ornamental Shrimps Neocaridina denticulata and Neocaridina palmata from Purbalingga Fish Market Aquariums - Srimurni Kusmintarsih Endang; Hassan Alsheikh Mahmoud Hanan; Husein Sastranegara Moh.; Syakuri Hamdan; Nuryanto Agus (E3S Web of Conferences)
The Neocaridina genus is one of the atyidae families that inhabit lakes, tributaries, ponds, rivers, and streams. Two species of Neocaridina have become popular in the Indonesian aquarium, namely N. denticulata and N. palmata. Neocaridina species are affected by ectoparasites, the same as another ornamental shrimp. The ectoparasites are to be found on the shrimp gills and surfaces. This study aimed to identify ectoparasites on the gill, and surfaces and, subsequently, to evaluate the infection rate between two species regarding sex, and organs. Neocaridina species were collected from the Purbalingga fish market. The univariate analysis described the variable and significance difference among the factors at a level (p<0.05). Two hundred samples were examined, and one hundred samples from each species. The results showed that 78% N. denticulata and 78% N. palmata were infected with no significant difference in the infection of the two species. Ectoparasites are found in two species namely sessile bdelloid rotifers, Vorticella sp., and Zoothamnium sp. Sessile bdelloid rotifers were detected in males and females of the two species. Higher infection by Vorticella sp. and Zoothamnium sp. were recorded in females of the two species. Sessile bdelloid rotifers were highly infected on the surfaces/cephalothorax of the two species while Vorticella sp. were highly infected on the gills of the two species. Zoothamnium sp. was not detected on the cephalothorax of the two species, these parasites species were host-specific to the gills of the two species. Vorticella sp and Zoothamnium sp. were not infected on the cephalothorax of N. denticulata.